A sporadic case of epidermodysplasia verruciformis in a young boy - Rita V Vora; Rahulkrishna Sureshkumar Kota; Rochit R Singhal; Shailee S Gandhi (Wolters Kluwer Medknow Publications, 2017)
Epidermodysplasia verruciformis (EV) is a rare disorder that is usually transmitted in an autosomal recessive manner, caused by human papillomavirus which presents with tinea versicolor-like or flat wart-like lesions. It has propensity for malignant transformation, especially squamous cell carcinoma. Here, we present a case of 7 year boy with complaints of asymptomatic hypopigmented macular lesions over the face, neck, and forearms. Histopathology was suggestive of EV and was given oral zinc, advised strict photoprotection.